The Mediating Role of Work-Life Balance in the Relationship Between Employee Engagement and Job Satisfaction Among Hotel Employees - Tasya Lindia Putri Ayu; Arif Adrian (Pt. Threeple Herphi Educate, 2026)
This study examines the mediating role of work-life balance in the relationship between employee engagement and job satisfaction among employees of Four Points by Sheraton Jakarta, Thamrin. A quantitative causal-associative survey design was employed, involving 49 employees who had worked at the hotel for at least one year. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. Internal consistency reliability and convergent validity were satisfactory; however, the Fornell-Larcker criterion was not fully met, suggesting possible overlap among the constructs and requiring cautious interpretation of the structural relationships. Employee engagement had positive effects on job satisfaction (β = 0.747, t = 6.462, p < 0.001) and work-life balance (β = 0.645, t = 5.853, p < 0.001). Work-life balance also had a positive effect on job satisfaction (β = 0.445, t = 3.584, p < 0.001). The indirect effect of employee engagement on job satisfaction through work-life balance was significant (β = 0.287, t = 2.933, p = 0.003). Because both the direct and indirect effects were significant, work-life balance was interpreted as a partial mediator. The findings suggest that hotel management should strengthen employee engagement while implementing work arrangements that help employees manage their work and personal responsibilities.